¿Y si trabajan en grupo...? : Interacciones entre alumnos, procesos sociales y cognitivos en clases universitarias de física - Cordero, Silvina (2002)
This paper presents some results of a case study about the characteristics of the interactions between pupils in groupworks, in the context of an innovative teaching experience of Physics at university level. Videorecordings were carried ou t during classes of the unit on Thermodynamics and some pupils from a focal group were interviewed. Analysis focused on group processes from the linguistic, social and cognitive perspectives. Results suggest that sharing cognitive processes by a group o f student, through reasoning and argumentation, may be an answer to the challenges of teaching practice at university level.